2018
DOI: 10.2135/cropsci2017.07.0442
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mislabeling on Genomic Selection in Cassava Breeding

Abstract: In plant breeding, humans occasionally make mistakes. Genomic selection is particularly prone to human error because it involves more steps than conventional phenotypic selection. The impact of human mistakes should be determined to evaluate the cost effectiveness of controlling human error in plant breeding. We used simulation to evaluate the impact of mislabeling, where marker scores from one plant are associated with the performance records of another plant in cassava (Manihot esculenta Crantz) breeding. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The Bitter-Group shows greater genetic diversity and less drift, followed by Admix-Group and NE_LandRaces, while the rest had less than 50, making them predisposed to genetic drift. However, it has been shown that small effective population size of a genetic pool indicates high LD and potential for improved prediction accuracy (Yabe et al 2018a , b ). Applying the 50/500 rule as described by Franklin and colleagues (Franklin and Frankham 1998 ), a genetic group’s effective population size of at least 50 individuals is necessary for conservation of genetic diversity in the short term and avoids inbreeding depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bitter-Group shows greater genetic diversity and less drift, followed by Admix-Group and NE_LandRaces, while the rest had less than 50, making them predisposed to genetic drift. However, it has been shown that small effective population size of a genetic pool indicates high LD and potential for improved prediction accuracy (Yabe et al 2018a , b ). Applying the 50/500 rule as described by Franklin and colleagues (Franklin and Frankham 1998 ), a genetic group’s effective population size of at least 50 individuals is necessary for conservation of genetic diversity in the short term and avoids inbreeding depression.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of average LD decay threshold to the standard threshold of 0.1 ( r 2 ) for all genetic pools shows a similar trend with average genetic pool’s LD decay having higher genetic distances across groups (Supplementary Figure 5b). Given the allogamous nature of cassava, the pattern of LD may reduce prediction accuracy, since LD is crucial for genomic selection (GS) breeding (Jannink 2010 ; Yabe et al 2018a , b ). However, the high LD observed in this study indicates potential for improved accuracy using this population for GS breeding.…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to post‐introduction hybridization between sweet and bitter cassava, and the inconsistent transfer of ethnobotanical knowledge of use‐category management to Africa (Bradbury et al ., 2013). The mislabeling of germplasm in Africa (Yabe et al ., 2018) may also have contributed to the observed difference. These differences were also observed with the distribution plots for the individuals assayed in our analysis for HCN in Latin American (bimodal distribution) and African (almost normally distributed) populations.…”
Section: Discussionmentioning
confidence: 93%
“…Accession mislabelling has been reported to reduce the genetic gain of cassava by up to 40% in Africa (Yabe, Iwata, and Jannink 2018). In order to address germplasm duplication in the Brazilian collection, we inferred genetic identity between accessions using an identity-by-state (IBS) analysis.…”
Section: Ibs Duplicate Identificationmentioning
confidence: 99%